Can online based learning activities improve learning outcomes in classroom teaching? - Jacob Wewer Albrechtsen, Nicolai (Improving University Science Teaching and Learning, 2023)
Students and teachers, in fact everybody, are facing an overload of information with a risk of disinformation as seen for example in the medical community (Steen, 2011). Access to information is thought to be ‘easy’, but access to accurate information may not be (Eppler & Mengis, 2008). I believe this is the case for science as well as education.